Atmospheric Cold Plasma Inactivation of Salmonella and Escherichia coli on the Surface of Golden Delicious Apples - Kilonzo-Nthenge, Agnes; Liu, Siqin; Yannam, Sudheer; Patras, Ankit (Frontiers in Nutrition, 2018)
The contamination of fruits with human pathogens is a reoccurring concern in the fresh produce industry. Atmospheric cold plasma (ACP) is a potential alternate to customary approaches for non-thermal decontamination of foods. In this study, the efficacy of a dielectric barrier discharge ACP system against Salmonella (Salmonella Typhimurium, ATCC 13311; Salmonella Choleraesuis, ATCC 10708) and Escherichia coli (ATCC 25922, ATCC 11775) was explored. For each bacteria, a two-strain mixture at 8 log10 CFU/ml was spot inoculated on the surface of Golden Delicious apples, air dried, and exposed to ACP at a fixed distance of 35 mm, input power of 200 W for 30, 60, 120, 180, and 240 s. Bacterial inactivation was achieved in all treatment times with highest reduction of 5.3 log10 CFU/cm2 for Salmonella and 5.5 log10 CFU/cm2 for E. coli. Our results showed that reductions were interrelated to exposure time and ranged from 1.3 to 5.3 and 0.6 to 5.5 log10 CFU/cm2 for Salmonella and E. coli, respectively. Salmonella and E. coli significantly decreased (>5.0 log) at 180 and 240 s as compared to 30, 60, and 120 s exposure. Microbial inactivation data was modelled by using Weibull distribution. These findings demonstrate the potential of ACP as a postharvest technology to effectively reduce pathogens on apples, with reference to Salmonella and E. coli.